The Effect of Organizational Culture and Leadership Style on Employees at Radio Televisao de Timor Leste. Empresa Publico (RTTL.EP), Timor-Leste - Januario Soares; Dian Indiyati; Astri Ghina (International Journal of Science and Society, 2021)
Organizational culture and leadership are part of human resources which are one of the capital and have a very important role for the success of a company or organization because good human resource management is the key to the successful achievement of the company's goals. The success of an organization in achieving its goals in addition to requiring a good organizational culture, also depends on the implementation of the leadership style. A strong leadership style in the organization is used to direct all available resources in achieving goals and optimizing success in a company. This study aims to determine to test and analyze the influence of Organizational Culture and Transformational Leadership Style on Employee Performance at RTTL.EP. The aspects studied are the employee's work culture, the leadership style of a leader, and the impact of the process of the two variables which will result in employee job performance. The phenomenon in this research is explored with quantitative methods. Data collection techniques are by distributing research questionnaires, interviews, and collecting secondary data. The sample taken was 180 samples of RTTL.EP employees. The results of this study are expected to be used as a work evaluation to improve organizational culture, leadership, and performance, this research can be used as a direction in improving employee performance at RTTL.EP so that it is always in line with the Vision and Mission of RTTL.EP, which is to provide quality programs to the audience.